Paraplegia New Insights - Mansoor Rayegani, Seyed (IntechOpen, 2023)
Paraplegia - New Insights reviews different and complementary aspects of one of the most common and catastrophic conditions. The book, edited and organized into five chapters, covers the most interesting and frequently encountered scientific material on spinal cord injury and paraplegia. It is hoped that readers will not only find answers to some of their questions but also gain a detailed understanding of paraplegia and holistic approaches to its treatment.